2017
DOI: 10.1159/000486859
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Intestinal Peptide Protects Salivary Glands against Structural Injury and Secretory Dysfunction via IL-17A and AQP5 Regulation in a Model of Sjögren Syndrome

Abstract: Objective: Sjögren syndrome (SS) is an autoimmune disease involving exocrine glands. Currently, drugs that can improve both abnormal immunity and exocrine gland function are needed. The study aimed to investigate the effect and mechanism of vasoactive intestinal peptide (VIP) on the immune response and exocrine gland function in SS. Methods: We investigated the effects of VIP on the immune response and secretory function of submandibular glands using NOD mice, and analyzed the expression of IL-17A and AQP5 (aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…IL-17 has been recently reported to play a role in epithelial–mesenchymal transition in SGECs from SS patients [ 70 ]. Vasoactive intestinal peptide (VIP) administration to NOD mice protects SG against injury and secretory dysfunction by downregulating Il-17 expression and upregulating Aqp5 expression [ 71 ]. Blocking IL-7-induced levels reduced SG inflammation and hypofunction [ 72 ], and upregulated AQP5 expression [ 73 ].…”
Section: Involvement Of Aqps In Sg Pathologiesmentioning
confidence: 99%
“…IL-17 has been recently reported to play a role in epithelial–mesenchymal transition in SGECs from SS patients [ 70 ]. Vasoactive intestinal peptide (VIP) administration to NOD mice protects SG against injury and secretory dysfunction by downregulating Il-17 expression and upregulating Aqp5 expression [ 71 ]. Blocking IL-7-induced levels reduced SG inflammation and hypofunction [ 72 ], and upregulated AQP5 expression [ 73 ].…”
Section: Involvement Of Aqps In Sg Pathologiesmentioning
confidence: 99%
“…Li et al showed that VIP treatment was able to reduce immune lesions in the exocrine glands and improve the secretory function of these glands by negatively regulating the expression of IL-17A in the exocrine glands. It also improved the secretory function of the exocrine glands by increasing the expression of AQP5, a protein that participates in the transport of water through the glandular epithelium [301].…”
Section: Other Autoimmune Disordersmentioning
confidence: 99%
“…Vasoactive intestinal peptide (VIP) is a 28-amino acid peptide that is extensively distributed in tissues, which exerts pleiotropic functions in multiple systems, such as the gastrointestinal [7], cardiovascular [8], nervous [9], and immune [10, 11] systems. Many studies have shown that VIP can be used as an immunomodulatory and anti-inflammatory factor that participates in regulating immune balance [10, 12]. It has been reported that VIP can effectively increase the number of Treg subpopulations while decreasing the number of Th17 subpopulations to improve inflammation in asthmatic mice by regulating Th17/Treg balance and VIP can also maintain the immune balance between Th17/Treg cells in the prevention and treatment of experimental autoimmune encephalomyelitis (EAE).…”
Section: Introductionmentioning
confidence: 99%